Algorithm of revitalization programme design for housing estates = Propozycja algorytmu programu rewitalizacji dla osiedli mieszkaniowych - Ostańska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Demographic problems, obsolescence of existing buildings, unstable economy, as well as misunderstanding of the mechanism that turn city quarters into areas in need for intervention result in the implementation of improvement measures that prove inadequate. The paper puts forward an algorithm of revitalization program for housing developments and presents its implementation . It also showed the effects of periodically run (10 years) three-way diagnostic tests in correlation with the concept of settlement management.
Keywords: rewitalizacja; działania naprawcze; osiedla mieszkaniowe; revitalisation; corrective actions; residential settlement